2015
DOI: 10.1111/petr.12628
|View full text |Cite
|
Sign up to set email alerts
|

PTSD in solid organ transplant recipients: Current understanding and future implications

Abstract: Posttraumatic stress symptoms (PTSS) are quite prevalent in transplant recipients, although full-scale posttraumatic stress disorder (PTSD) may not be that common. Those symptoms have been linked to poor transplant outcomes, perhaps owing to nonadherence to medications and other recommendations, brought about by the avoidance dimension of the PTSD/PTSS construct (patients may avoid taking their medications because they serve as reminder of the emotionally traumatic event – the transplant). Since it is possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 61 publications
(93 reference statements)
0
33
0
1
Order By: Relevance
“…A study by Karapolat and colleagues in adult HTx recipients demonstrated that functional capacity correlated with depression and anxiety. and therefore there may be diagnoses relevant to HTx outcomes that were not assessed (ie, post-traumatic stress disorder 44,45 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Karapolat and colleagues in adult HTx recipients demonstrated that functional capacity correlated with depression and anxiety. and therefore there may be diagnoses relevant to HTx outcomes that were not assessed (ie, post-traumatic stress disorder 44,45 ).…”
Section: Discussionmentioning
confidence: 99%
“…This, combined with the limitations inherent to ICD coding and variation in the availability of psychiatric resources across centers, likely results in the underestimation of psychiatric diagnoses in our study. It is important to acknowledge that the psychiatric disorders included in our analysis were not exhaustive and therefore there may be diagnoses relevant to HTx outcomes that were not assessed (ie, post‐traumatic stress disorder 44,45 ). Meaningful levels of psychosocial risk also occur in pediatric HTx recipients well‐beyond the transplant admission 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, pediatric recipients are at an important stage of physical and mental development. [13] Some complications may occur after liver transplant. Long-term use of immunosuppressants may also cause side effects to the body.…”
Section: Discussionmentioning
confidence: 99%
“…An important area for further consideration is whether posttraumatic stress may be a factor in poor outcomes during transition. Posttraumatic stress symptoms and posttraumatic stress disorder have emerged as risk factors for nonadherence in populations with chronic medical needs [27][28][29][30][31]. Indeed, recent work utilizing a representative sample of the general population demonstrated the profound impact of trauma exposure on functional impairment in those who experienced a traumatic event before the age of 18 years [32].…”
Section: Mental Healthmentioning
confidence: 99%
“…Indeed, recent work utilizing a representative sample of the general population demonstrated the profound impact of trauma exposure on functional impairment in those who experienced a traumatic event before the age of 18 years [32]. In the context of special healthcare needs, the avoidance dimension of posttraumatic stress symptoms has been invoked as a potential mechanistic explanation for the reported association between posttraumatic stress symptoms and nonadherence [28,29,31]. Such nonadherence can lead to worsening medical outcomes and complications that, in turn, may lead to re-traumatization and further avoidance [33,34].…”
Section: Mental Healthmentioning
confidence: 99%